The effect of Campylobacter jejuni and Campylobacter coli colonization on the gut morphology, functional integrity, and microbiota composition of female turkeys - Rzeznitzeck, Janina; Breves, Gerhard; Rychlik, Ivan; Hoerr, Frederic J; von Altrock, Alexandra; Rath, Alexandra; Rautenschlein, Silke (Gut pathogens, 2022)
BACKGROUND: Campylobacter (C.) species are the most common bacterial cause of foodborne diarrhea in humans. Despite colonization, most animals do not show clinical signs, making recognition of affected flocks and disruption of the infection chain before slaughter challenging. Turkeys are often cocolonized with C. jejuni and C. coli. To understand the pathogen-host-interaction in the context of two different Campylobacter species, we compared the colonization patterns and quantities in mono- and co-colonized female commercial turkeys. In three repeated experiments we investigated the impact on gut morphology, functional integrity, and microbiota composition as parameters of gut health at seven, 14, and 28 days post-inoculation. RESULTS: Despite successful Campylobacter colonization, clinical signs or pathological lesions were not observed. C. coli persistently colonized the distal intestinal tract and at a higher load compared to C. jejuni. Both strains were isolated from livers and spleens, occurring more frequently in C. jejuni- and co-inoculated turkeys. Especially in C. jejuni-positive animals, translocation was accompanied by local heterophil infiltration, villus blunting, and shallower crypts. Increased permeability and lower electrogenic ion transport of the cecal mucosa were also observed. A lower relative abundance of Clostridia UCG-014, Lachnospiraceae, and Lactobacillaceae was noted in all inoculated groups compared to controls. CONCLUSIONS: In sum, C. jejuni affects gut health and may interfere with productivity in turkeys. Despite a higher cecal load, the impact of C. coli on investigated parameters was less pronounced. Interestingly, gut morphology and functional integrity were also less affected in co-inoculated animals while the C. jejuni load decreased over time, suggesting C. coli may outcompete C. jejuni. Since a microbiota shift was observed in all inoculated groups, future Campylobacter intervention strategies may involve stabilization of the gut microbiota, making it more resilient to Campylobacter colonization in the first place.
Keywords: Morphology; Microbiota composition; Gut health; Campylobacter; Turkey; Ussing chambers